Studi Kualitas dan Potensi Pemanfaatan Airtanah Dangkal di Pesisir Surabaya Timur - Wahyudi, Wahyudi; Setiyono, Arief; Jayanthi, Onie Wiwid (BRIN Publishing, 2014)
The eastern part of coastal area is one of the fast growing urban area in Surabaya. Increasing in population and industrial growth have driven increasing demands for natural resources, particularly water. The objectives of this study are to identify the quality of the coastal groundwater through insitu measurement and laboratory analysis, and to find out its potential to be utilized as a source of water for coastal aquaculture. Groundwater samples from 70 sampling stasiun have been taken from east Surabaya coastal area. Measurements of the temperature, pH, and dissolved oxygen of the samples were carried out directly insitu, and measurements of concentration of nitrate, nitrit, ammonia, sulphide, and posphate conducted in the Environmental Laboratory of ITS. The results show that coastal groundwater in west part of the study area, in only very small area, can be used as a drinking water, and in almost all area of the east Surabaya coastal area is not permitted. In the central and south part can be utilized as a source of the coastal aquaculture, however in the north part is not potential, in the central area is medium, and in the south part is categorized as a high potential.